Erratum to the prevalence of pulmonary hypertension in patients with obesity hypoventilation syndrome: a prospective observational study - Almeneessier, Aljohara S.; Nashwan, Samar Z.; Al-Shamiri, Mostafa Q.; Pandi-Perumal, Seithikurippu R.; BaHammam, Ahmed S. (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Erratum to: J Thorac Dis 2017;9:779-788.